Time Multiplexing of Currents for Magnetic Particle Inspection. Issue 6 (2nd November 2022) - Staněk, Pavel; Škvor, Zbyněk
ABSTRACT: This article concerns magnetization methods for detecting arbitrary oriented defects by magnetic particle inspection. The authors propose a new method of magnetization with omnidirectional detection ability requiring only a single-channel DC or AC power supply. The detection of all defects by the new method can be achieved during a single testing (spraying) cycle.